Developments in the treatment of carcinoid syndrome – impact of telotristat - Chan DL; Singh S (Dove Medical Press, 2018)
David L Chan, Simron Singh Odette Cancer Centre, Sunnybrook Health Sciences Centre, Toronto, ON, Canada Abstract: Carcinoid syndrome occurs in 20% of patients with neuroendocrine tumors, and serotonin is usually the main causative hormonal peptide. Carcinoid syndrome, and particularly diarrhea, can significantly impact patients’ quality of life. Somatostatin analogs (SSAs) are the mainstay of treatment, but are unable to ameliorate symptoms in all patients due to dose-limiting side effects and tachyphylaxis. Telotristat is a novel oral inhibitor of tryptophan hydroxylase, which is the rate-limiting enzyme in serotonin synthesis. A Phase III placebo-controlled trial of telotristat etiprate (orally at 250 mg three times a day) showed a significant decrease in the frequency of bowel motions in treated patients with diarrhea from carcinoid syndrome. The main side effects were gastrointestinal symptoms, deranged liver function tests and depression. Treatment with 500 mg three times a day also decreased stool frequency, but was associated with more nausea and mood disturbances. Telotristat, therefore, represents a valuable option in the management of carcinoid syndrome diarrhea refractory to SSAs, and the US Food and Drugs administration approved its use for this indication in March 2017. However, its role in somatostatin-naïve patients and in the treatment of other carcinoid syndrome symptoms (flushing and abdominal pain) remains unknown. Further research should focus on these issues as well as the safety of continuing telotristat in the context of other systemic antineoplastic therapies. Keywords: neuroendocrine, carcinoid, telotristat, diarrhea